Effect of Ninjin’yoeito on the Loss of Skeletal Muscle Function in Cancer-Bearing Mice - Ohsawa, Masahiro; Maruoka, Junya; Inami, Chihiro; Iwaki, Anna; Murakami, Tomoyasu; Ishikura, Kei-ichiro (Frontiers in Pharmacology, 2018)
Ninjin’yoeito (NYT), a traditional Japanese Kampo medicine formula, is used as a remedy for conditions, and physical weakness. Cancer cachexia is seen in advanced cancer patients and is defined by an ongoing loss of skeletal-muscle mass that leads to progressive functional impairment. In the present study, we examined the hypothesis whether NYT improves the functional loss of skeletal muscle cancer cachexia. Male C57/BL 6J mice with B16F6 melanoma tumor showed decreased expression of myosin heavy chain (MHC) in the gastrocnemius muscle. Moreover, the expression of SOCS3 and phosphorylated STAT3 and AMPK was increased, and the expression of phosphorylated 4E-BP1 was decreased in the gastrocnemius muscle of tumor-bearing mice. These data suggested that amino acid metabolism was altered in tumor-bearing mice, which were normalized by the NYT intervention. The present study showed that NYT might be a novel therapeutic option for the treatment of sarcopenia occurring cancer cachexia.